User Mobile Payment Behavior Using Technology Acceptance Model (TAM): Study of "Dana" E-Wallet Users - Isrososiawan, Safroni; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2019)
This study aims to determine the effect perceived usefulness on Mobile Payment and perceived ease of use. This research uses a quantitative approach with a questionnaire data collection tool. Population of this study is the graduate students of the Universitas Pendidikan Indonesia with a total sample of 100 students, a quota sampling method applied. Hypotheses of “DANA” application analyzed by using multiple regression analysis. The findings in this study indicate that perceived easefulness and perceived ease of use had a positive and significant effect on mobile payment.